Anesthetic Considerations in a Patient with Myotonic Dystrophy for Hip Labral Repair - Ramon Go; David Wang; Danielle Ludwin (Case Reports in Anesthesiology)
Myotonic Dystrophy (DM) affects multiple organ systems. Disorders such as hyperthyroidism, progressive musculoskeletal weakness, cardiac dysrhythmias, hypoventilation, and cognitive-behavioral disorders may be present in these patients. Thorough preoperative assessment and anesthetic planning are required to minimize the risk of anesthetic complications. Patients with DM can exhibit exquisite sensitivity to sedatives, neuromuscular blocking agents, and volatile anesthetics, resulting in potential postoperative complications. There is limited literature available on successful anesthetic techniques for the DM patient. We present this case report to add to our current fund of knowledge.